Profil Kadar HbA1c dan Karakteristik Klinis Pasien Diabetes Melitus Tipe 2 di Poli Penyakit dalam RSUD Cut Meutia Aceh Utara - Khairun Nisa; Zubir Zubir; Rizka Sofia (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Chronic disease caused by increased blood sugar levels and potentially causing many complications especially when uncontrolled conditions are known as diabetes mellitus. Glycosylated hemoglobin examination is a reliable method in evaluating long-term glycemic control because it is not affected by daily fluctuations and reflects glucose levels for 120 days. The province with the 10th highest number of diabetes mellitus cases in 2018 was Aceh. One of the districts in Aceh, namely North Aceh, is the area with the highest incidence of cases. This study aims to describe HbA1c levels and characteristics of type 2 diabetes mellitus patients at Cut Meutia Regional Hospital, North Aceh in 2023. Using a descriptive cross-sectional design, 77 patients were selected through purposive sampling. Data were collected from laboratory results and MMAS-8 and MIAS-8 questionnaires. The results showed that most patients had uncontrolled HbA1c levels (90.9%), uncontrolled HbA1c men (91.7%), 56–65 years old (40.3%), had pre-hypertension blood pressure (83.1%), and medication compliance in the moderate category (54.5%). This can be concluded that cases of diabetes with uncontrolled glycosylated hemoglobin levels are men.